Does Relationship Satisfaction Always Mean Satisfaction? Development of the Couple Relationship Satisfaction Scale. (2019) - Cepukiene, Viktorija
Abstract: This article presents the development of an instrument measuring relationship satisfaction, based on the theory that separates 'relationship quality' from 'satisfaction' concerning the semantic meaning of the concepts, and to evaluate psychometric properties of the new measure. Two studies were conducted in order to investigate the psychometric properties of the new scale, with 372 and 1, 185 participants taking part in Study 1 and Study 2 respectively. Results revealed that the new scale has two-factor structure, adequate internal consistency reliability, and convergent, discriminant and known-groups validity.